CH3OH optically pumped by a (CO2)-C-13 laser: new laser lines and assignments - Costa, L. F. L.; Moraes, João Carlos Silos [UNESP]; Cruz, F. C.; Viscovini, R. C.; Pereira, D. (Springer, 2007)
We report 12 new THz (far-infrared) laser lines from methanol (CH3OH), ranging from 58.1 mu m (5.2 THz) to 624.6 mu m (0.5 THz). A(13) CO2 laser of wide tunability (110 MHz) has been used for optical pumping, allowing access to previously unexplored spectral regions. Optoacoustic absorption spectra were used as a guide to search for new THz laser lines, which have been characterized in wavelength, polarization, offset, relative intensity, and optimum operation pressure. For 20 laser lines previously observed, we have measured the absorption offset with respect to the (CO2)-C-13 laser line center.